Diagnostic benefits of presurgical fMRI in patients with brain tumours in the primary sensorimotor cortex - Wengenroth, Martina; Blatow, Maria; Günther, Janine; Akbar, Michael; Tronnier, V. M.; Stippich, C. (European radiology, 2011)
Reliable imaging of eloquent tumour-adjacent brain areas is necessary for planning function-preserving neurosurgery. This study evaluates the potential diagnostic benefits of presurgical functional magnetic resonance imaging (fMRI) in comparison to a detailed analysis of morphological MRI data.